2019
DOI: 10.1155/2019/8258307
|View full text |Cite
|
Sign up to set email alerts
|

Stingless Bee Honey Improves Spatial Memory in Mice, Probably Associated with Brain-Derived Neurotrophic Factor (BDNF) and Inositol 1,4,5-Triphosphate Receptor Type 1 (Itpr1) Genes

Abstract: This study was conducted to evaluate the effects of stingless bee honey (SBH) supplementation on memory and learning in mice. Despite many studies that show the benefits of honey on memory, reports on the nootropic effects of SBH are still lacking, and their underlying mechanism is still unclear. SBH is a honey produced by the bees in the tribe of Meliponini that exist in tropical countries. It features unique storage of honey collected in cerumen pots made of propolis. This SBH may offer a better prospect for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, honey was widely used for wound healing, as a food preservative, and against gastrointestinal illnesses [ 12 ]. According to recent literature, honey has revealed the presence of several beneficial effects for human health such as antibacterial [ 13 ], antioxidant, anti-inflammatory [ 14 ], and cardioprotective effects [ 15 ], with potentials as antiobesity [ 16 ] and neuroactivation associated with spatial memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional common properties of SBH that were mentioned above, a recent study showed that one of the components of SBH (i.e., phenylalanine) may be able to trigger the upregulation of brain-derived neurotrophic factor ( BDNF ) and inositol 1,4,5-triphosphate receptor type 1 ( ITPR1 ) [ 26 ], which are genes involved in synaptic function [ 77 , 78 ]. Therefore, SBH displayed capabilities in improving spatial working memory, spatial reference memory and memory consolidations.…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…Prior to dilution, the SBH was allowed to be at room temperature and freshly prepared with normal saline (2.0 g/kg body weight) each time it was administered. The dose (2.0 g/kg body weight) was chosen based on previous study (Mustafa et al, 2019;Sahlan et al, 2020). MET (250 mg/kg body weight) was dissolved in distilled water just before oral administration on each day.…”
Section: Preparation Of Stingless Bee Honey (Sbh)mentioning
confidence: 99%